Uniformly a Posteriori Error Estimate for the Finite Element Method to a Model Parameter Dependent Problem (Journal of Computational Mathematics, 2018)
This paper proposes a reliable and efficient a posteriori error estimator for the finite element methods for the beam problem. It is proved that the error can be bounded by the computable error estimator from above and below up to multiplicative constants that do neither depend on the mesh size nor on the thickness of the beam.
Keywords: The beam problem; A posteriori error estimator; Finite element method.